Chlorophyll-a concentration inversion based on the modified Quasi-Analytical Algorithm and Sentinel-3 OLCI in Daihai Lake, China. Issue 3 (7th December 2021) - Lu, Zhao; Duan, Huajie; Wang, Daqing; Cao, Jianwu; Du, Guoli; Deng, Zhengdong; Wang, Guangyuan; Xu, Haoli; Zhao, Xiaoning; Shi, Yue
Abstract: The Quasi-Analytical Algorithm (QAA) is effective in retrieving water inherent optical properties (IOPs) from remote sensing spectral reflectance and has wider applications in studies of the open ocean and coastal waters than of inland waters. This research aimed to modify the QAA model based on measured field spectral reflectance and absorption coefficients to render it applicable to studies of Daihai Lake, China. The improvements mainly included the reference wavelength selection, the power index of the particle backscattering coefficient and the exponential slope of the absorption coefficient of the colored detrital matter estimation. The average relative error between the inverse and measured absorption coefficients was less than 20%. A linear model was established between the phytoplankton absorption coefficient at a wavelength of 674 nm ( a ph (674)) and the chlorophyll-a (Chl-a) concentration, with a determination coefficient of 0.88. Additionally, the modified Quasi-Analytical Algorithm (MQAA) model was applied to the Ocean and Land Color Instrument (OLCI) data aboard the Sentinel-3 satellite. Finally, a spatial distribution map for the Chl-a concentrations in Daihai Lake on August 10, 2017, was drawn and the mid-eutrophication area was found to occur in the north and border. HIGHLIGHTS: The quasi-analytical algorithm (QAA) is modified to MQAA. The MQAA is useful in application to OLCI data for chlorophyll-a concentration retrieval. The application of MQAA in Daihai is targeted.